Crisis management during anaesthesia: difficult intubation. Issue 3 (2nd June 2005) - Paix, A D; Williamson, J A; Runciman, W B
Abstract : Background: Anaesthetists may experience difficulty with intubation unexpectedly which may be associated with difficulty in ventilating the patient. If not well managed, there may be serious consequences for the patient. A simple structured approach to this problem was developed to assist the anaesthetist in this difficult situation. Objectives: To examine the role of a specific sub-algorithm for the management of difficult intubation. Methods: The potential performance of a structured approach developed by review of the literature and analysis of each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual management as reported by the anaesthetists involved. Results: There were 147 reports of difficult intubation capable of analysis among the first 4000 incidents reported to AIMS. The difficulty was unexpected in 52% of cases; major physiological changes occurred in 37% of these cases. Saturation fell below 90% in 22% of cases, oesophageal intubation was reported in 19%, and an emergency transtracheal airway was required in 4% of cases. Obesity and limited neck mobility and mouth opening were the most common anatomical contributing factors. Conclusion: The data confirm previously reported failures to predict difficult intubation with existing preoperative clinical tests and suggest an ongoing need to teach a pre-learned strategy to deal with difficult intubation and any associated problem with ventilation. An easy-to-follow structured approach to these problems is outlined. It is recommended that skilled assistance be obtained (preferably another anaesthetist) when difficulty is expected or the patient's cardiorespiratory reserve is low. Patients should be assessed postoperatively to exclude any sequelae and to inform them of the difficulties encountered. These should be clearly documented and appropriate steps taken to warn future anaesthetists.